Respuesta :

M=(-22)

m+(-10)=-33
add 10 to -33
M=(-22)

Answer: ⇒ m=-23

________________________________________________________

Step-by-step explanation:

First you had to add by 10 from both sides of equation.

[tex]m-10+10=-33+10[/tex]

Simplify it's should be the right answer.

[tex]m=-23[/tex]

____________________________________________________

Hope this helps!

Thank you for posting your question at here on brainly.

Have a great day!

_______________________________________________________


ACCESS MORE